Analog Circuits - Wu, Yuping (IntechOpen, 2013)
The invariable motif for analog design is to explore the new circuit topologies, architectures and CAD technologies to overcome the design challenges coming from the new applications and new fabrication technologies. In this book, a new architecture for a SAR ADC is proposed to eliminate the process mismatches and minimize the errors. A collection of DG-MOSFET based analog/RFICs present the excellent performance; the automated system for a passive filter circuits design is presented with the local searching engaging; interval analysis is used to solve some problems for linear and nonlinear analog circuits and a symbolic method is proposed to solve the testability problem.